Analysis of the Pro- and Anti-Inflammatory Cytokines Secreted by Adult Stem Cells during Differentiation - Amy L. Strong; Jeffrey M. Gimble; Bruce A. Bunnell (Hindawi Limited, 2015)
Adipose-derived stromal/stem cells (ASCs) are adult stem cells that have the potential to differentiate into mesenchymal lineage cells. The abundance of ASCs in adipose tissue and easy accessibility with relatively little donor site morbidity make them attractive candidate cells for tissue engineering and regenerative medicine. However, the underlying inflammatory process that occurs during ASC differentiation into adipocytes and osteoblast has not been extensively investigated. ASCs cultured in osteogenic and adipogenic differentiation medium were characterized by oil red o staining and alizarin red staining, respectively. ASCs undergoing osteogenic and adipogenic differentiation were isolated on days 7, 14, and 21 and assessed by qRT-PCR for the expression of pro- and anti-inflammatory cytokines. ASCs undergoing osteogenic differentiation expressed a distinct panel of cytokines that differed from the cytokine profile of ASCs undergoing adipogenic differentiation at each of the time points analyzed. Mapping the cytokine expression profile during ASC differentiation will provide insight into the role of inflammation in this process and identify potential targets that may aid in enhancing osteogenic or adipogenic differentiation for the purposes of tissue engineering and regenerative medicine.